EVALUATION OF THE RESULTS OF NON-SURGICAL TREATMENT OF FEMURFRACTURES IN CHILDREN AT SHAHID BEHESHTI HOSPITAL IN YASUJ, BETWEEN 2011 TO 2016 - Mohammadi, H. R.; Rafiee, A.; Motlagh, A. H. (University of Eloued جامعة الوادي, 2018)
Introduction: Femoral shaft fracture is fairly common in children and due to the potential risk of bleeding and shock, it is important to diagnose and treat appropriate and timely treatment of this fracture. The femur bone is the largest bone in the body and has complex anatomy and is usually followed by direct and indirect severe trauma such as car crashes or falling from the height of the fracture. Materials and methods: All patients who were admitted to the orthopedic department of Yasuj Shahid Beheshti Hospital between 2011 and 2016 were identified. The total number of these patients was more than one hundred cases, of which there were some cases in the registration of the diagnosis in the case, and some were not referred to the hospital after the discharge from the hospital, which were excluded from the study.76 patients were examined, of which 26 were female and 50 were boys. The lowest age of patients was 15 days and the highest age was 15 years. Results: In terms of the mechanism of fracture, the most commonly reported car accident (34%) and after falling (falling) are 28%. Unusual mechanisms such as pathologic fracture (4%) or birth Fix (2%) or child abuse (2%) and fracture during physiotherapy (2%) make up a total of 10% of the mechanisms. The most common fracture age is in the age group of 2-10 years (66%), 10-15 years old (28%) and under 2 years old (6%). Defeat in boys (68%) is more than girls (32%) appear. Discussion: In this study, 88% of patients were treated with cure and 12% with surgical procedures, patients treated with surgery, two groups: 1) those who have cured a remedy fail.2) Adolescent ages, usually with fractures associated with displacement.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Femur, Fracturesin Children, Shahid Beheshti Hospital